Propositions and future directions of marketers’ relationship effectiveness in mergers and acquisitions integration - Jedin, Mohd. Haniff; Md Saad, Norsafinas (Universiti Utara Malaysia, 2012)
Research on marketing integration related to mergers and acquisitions (M&A) has paid little attention to the combination of similar resources between two similar departments, particularly in the M&A context. Furthermore, existing research does not clearly demonstrate the role of relationship among marketers within the amalgamation process between acquirer and target firm.Hence, this paper addresses a few propositions that relate to strengthening the relationship effectiveness among the marketers in both firms, which at the same time uphold the M&A performance. Collaboration and interaction are proposed as drivers to increase optimistic relationship among the marketers.A quantitative research design is suggested as this method is not popular compared to qualitative methods such as case study, event-study and longitudinal approach in M&A.Drawing from the extant literature, propositions are developed and future directions are presented elaborating success factors to improve M&A integration performance.